Directional and omnidirectional edge enhancement based on radial Hilbert transform of Gabor filter. Issue 9 (11th April 2016) - Wang, Ke
Abstract : A directional and omnidirectional edge enhancement method is proposed based on radial Hilbert transform (RHLT) of directional Gabor filter (DGF). A new transfer function is introduced to develop a new RHLT that can be rotated to enhance edges along the specified direction. Furthermore, to increase the edge response at the specified direction and suppress noise, DGF with the centre frequency being at the direct current component, is designed to be radial Hilbert transformed.